Transnational spaces of education as infrastructures of im/mobility - Jana M. Kleibert (Transactions of the Institute of British Geographers, 2021)
How do transnational education and international student mobilities intersect? Drawing on geographical literatures on knowledge mobilities and migration infrastructures, offshore campuses are conceptualised as infrastructures of im/mobilities, which are simultaneously embedded within global networks and situated within regional migration regimes. Based on qualitative research on offshore campuses in Southeast Asia, I presents a systematic typology of how offshore campuses and international student mobilities intersect. It is shown how mobile universities play a complex and situated role in reconfiguring international student mobilities and how their material and discursive spaces are sites of circulation and containment. By developing an infrastructures perspective that takes universities as brokers and campuses as the sites of brokerage into consideration, the study advances geographical knowledge on globalising education and mobilities.
Keywords: 710; infrastructures; international branch campus; migration; Southeast Asia; student mobilities